Street politics in the age of austerity : from the Indignados to Occupy - Angelovici, Marcos; Dufour, Pascale, 1971-; Nez, Héloïse (Protest and social movements, 2016)
The past few years have seen an unexpected resurgence of street-level protest movements around the world, from the uprisings of the Arab Spring to the rise of the anti-austerity Indignados in Spain and Greece to the global spread of the Occupy movement. This collection is designed to offer a comparative analysis of these movements, setting them in international, socio-economic, and cross-cultural perspective in order to help us understand why movements emerge, what they do, how they spread, and how they fit into both local and worldwide historical contexts. As the most significant wave of mass protests in decades continues apace, this book offers an authoritative analysis that could not be more timely.